PENGARUH UKURAN KOMITE AUDIT, AUDIT EKSTERNAL, JUMLAH RAPAT KOMITE AUDIT, JUMLAH RAPAT DEWAN KOMISARIS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA (Studi Empiris perusahaan manufaktur yang terdaftar di BEI tahun 2012-2014) - Felicia Marsha; Imam Ghozali (Diponegoro Journal of Accounting, 2017)
This study aims to test the effect of audit commitee, eksternal auditor, frequency of audit commitee meetings, frequency of board commissioners meetings and institusional ownership of earnings as dependent variable. Type of data used in this study is secondary data. The population of the study is all manufacture companies listed in Indonesia Stock Exchange. To collect the sample, the writer employed purposive sampling method and applied criteria listed in Indonesia Stock Exchange, reported annually subsequently from 2012-2014 in Indonesia Stock Exchange. There was audit commitee, eksternal auditor, frequency of audit commitee meetings, frequency of board commissioners meetings and institusional ownership variable in financial report.The result of this study shows that audit commitee and audit commitee effectiveness significantly influenced the earnings management activities. Meanwhile, eksternal auditor, board commissioners effectiveness and institusional ownership did not influence earnings management activities in maufacture companies in Indonesia from 2012-2014.